Análisis de la consistencia y coherencia de los planes de desarrollo y ordenamiento territorial de los cantones Loja, Machala y Zamora Zona 7 - Castillo Ojeda, Valeria del Cisne (2018)
Abstract:The research arises from the need to know the consistency and coherence of development plans and territorial ordering, established in Ecuador as planning instruments from the year 2008. Considering for the analysis, the cantonal PDOTs belonging to the Planning Zone 7 (Loja, Machala and Zamora), the evaluation of the plans is done through integrated analysis matrices, which allow to quantitatively assess the consistency and coherence indexes, as well as content indexes and compatibility with the National Plan for Good Living and Zonal Agenda 7. Obtaining as a result, at a general level, the indexes in Zone 7 are low, being the PDOT of the Loja canton the one that presents the highest indexes in consistency and coherence, followed by the PDOT of the Machala canton and the PDOT of the canton Zamora that weighs at its low consistency and coherence indexes it obtains a higher content index.